MINERAL RESOURCE GOVERNANCE AND POLICY FRAMEWORKS IN AFRICA; A CASE STUDY OF EAST AFRICA COUNTRIES- KENYA - ABDINOOR, MAALIM HUSSEIN (IJRDO - Journal of Business Management, 2025)
Mineral resources are important contributors to the global economy and societal wellbeing. Directly, they provide employment, revenue and taxes through the extraction, processing and sale of minerals. Indirectly, they are essential to all modern industries, including: energy, manufacturing, construction, biotic and abiotic resource extraction and agriculture. The principle that ‘one cannot understand the value of what they have until they measure it’ is particularly relevant with critical raw materials (CRMs).CRM is a concept that categorizes select resources (mainly minerals and metals) as critical in the sense that, at a national level, they are essential and difficult to replace, and their supply is prone to disruption. It is becoming increasingly recognized that the continuity of civilization and living standards as some have envisioned them in the future is constrained by the quality and quantity of various minerals. National-level strategic planning, including energy policy, foreign relations policy, geopolitical operations, national defense, education and infrastructure planning, among others, all require knowledge of the requirement and supply of raw materials towards a practical strategic implementation. Hence, a national CRM framework is essential for a prosperous, productive and stable future. To effectively manage the supply and use of CRMs, it is important to comprehend both their formal (e.g., economic) and informal (e.g., social and environmental) values, and to measure and monitor these values effectively over time. This study examines international practices and methodologies as components of a comprehensive CRM framework. We then propose a prototype CRM framework for East African Countries particularly in Kenya where such a framework is not in place.All CRM frameworks feature one or more rating schemes to identify the degree of criticality of raw materials. The actual rating metrics are divided into dimensions (or factors), such as: socio-economic importance, technological importance, environmental, social and governance risks. Such dimensions are important due to the following reasons.Delineating criticality from non-criticality: by rank-ordering CRMs based on various factors, a country can identify which ones are the most important for its economy, industry and national security. This information can help policymakers prioritize the development of domestic production and secure a stable supply of CRMs.Assessing resource sustainability and supply stability: by rating CRMs based on environmental, social and ethical factors, a country can assess the sustainability of its resource use and identify areas for improvement. This information can help policymakers develop strategies to mitigate resource depletion, and supply chain disruption, minimize negative environmental and social impacts, and promote responsible resource management.Supporting informed decision-making: an ordered ranking of CRMs provides quantitative and qualitative information to governmental bodies, industry and other stakeholders to support informed decision-making, including strategic planning. This information can help stakeholders make informed choices about the sources and types of CRMs they use and the sustainability of their resource use.Promoting transparency and accountability: adopting suitable business ethical dimensions, such as through a corporate social responsibility framework, enables a country to promote transparency and accountability in its resource use and supply chains. This approach can help reduce illicit financial flows, corruption, and abuse of power, while increasing trust and confidence in the resource sector.Innovation and investment opportunities: a CRM framework enables a nation to establish policy conditions that foster innovation and investment in key activities such as measuring, monitoring, sustainability, extracting, responsible processing, and efficient use of CRMs.Findings from this study underscores the necessity of a structured CRM framework in Kenya to effectively manage the complexities of resource management, economic ground, and sustainability. Integrating these frameworks into national policies can enable Kenya to secure a sustainable, economically viable, and environmentally responsible future. Such strategic initiatives are important for national security, industrial policy, structural transformation, and economic stability, as well as aligning with global initiatives for responsible sourcing and climate change.